Reconciliation, Nations and Churches in Latin America - Maclean, Iain S. (Taylor & Francis, 2006)
This book examines the recent phenomenon in Latin America of national Truth and Reconciliation commissions. Few studies have examined the role of Churches or religion in political processes that proclaim valued theological terms as their agenda - truth, forgiveness, and reconciliation. This book questions the role of religion, specifically of established Churches. The impact of such reconciliation commissions on Indigenous Native Americans is also examined, as is the role of women and how both commissions and Churches or religions were challenged by their experiences. The contributors offer differing perspectives on one or more national truth and reconciliation processes and thus offer a collection that serves as valuable source for the disciplines of Religious Studies, Ethics, Theology, Political Science, Social Sciences and Women's Studies.